Remnants of the Dutch Infrastructure in Banda Aceh During the Independence Revolution - Muhjam Kamza; Farhan Fadillah; M Yusrizal (IHiS (Indonesian Historical Studies))
The feud between the Dutch and Indonesia again peaked after Indonesia proclaimed independence on August 17, 1945. War broke out in almost every region in Indonesia, Aceh was one of them. The basis of the hatred of the Acehnese towards the Dutch which grew under the spirit of jihad fisabilillah [war in the way of Allah] made the Veranda of Mecca was never negligent in opposing the Dutch company. Uniquely, the prolonged war that erupted in Aceh did not affect the Dutch heritage buildings in Banda Aceh as the epicenter of the resistance. This study examines the function of the infrastructure of the Dutch colonial remains in Banda Aceh during the Indonesian Independence Revolution. The historical research method is emphasized on utilizing primary sources in the form essays compiled by historical actors and witnesses who lived during the independence revolution, as well as Dutch documents in the form of photographs and maps. According to the result, the Dutch heritage infrastructure in Banda Aceh during the independence revolution did not find any damage caused by war and was used for various revolutionary purposes. These buildings are generally used as the initial function and some of them are used according to the revolutionary war. However, the practice of vandalism in the form of crossing out and pasting information dissemination stickers often took place in the buildings at that time.